MUAC Z-Score: Tool for Early Detection of Child Malnutrition - Alvarado Álvarez, Alexandra María (2025)
The objective of this study is to analyze the importance of the MUAC Z-Score tape as a tool for the early detection of malnutrition in children under five years of age. A qualitative bibliographic review was conducted, applying specific inclusion criteria and considering scientific articles published between 2015 and 2025 in indexed databases. The results indicate that the MUAC Z-Score tape is a valid, economical, and practical tool, especially in rural areas where access to traditional anthropometric equipment is limited, allowing for a rapid identification of undernutrition and overnutrition through the measurement of mid-upper arm circumference. In conclusion, the implementation of MUAC Z-Score in community health programs can significantly improve the early detection of child malnutrition, although institutional support is needed to maximize its impact on reducing associated morbidity and mortality.